2006
DOI: 10.1590/s0103-84782006000200057
|View full text |Cite
|
Sign up to set email alerts
|

Broiler adaptation to post-hatching period

Abstract: In the latest years more attention has been given to mechanisms for bird adaptation at post-hatching period by management of environmental conditions and formulations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
(35 reference statements)
0
18
0
7
Order By: Relevance
“…At hatching, the gastrointestinal system is microorganism‐free. But after hatching, a significant number of microorganisms invade and colonize the gastrointestinal tract from mouth to caecum (Maiorka et al., 2006). Also, the immune system of the bird is partly developed at hatching.…”
Section: Discussionmentioning
confidence: 99%
“…At hatching, the gastrointestinal system is microorganism‐free. But after hatching, a significant number of microorganisms invade and colonize the gastrointestinal tract from mouth to caecum (Maiorka et al., 2006). Also, the immune system of the bird is partly developed at hatching.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion could be due to the fact that proteins of egg white are badly digested and assimilated in the first 72 hours post-hatching. In agreement with these results, the gastrointestinal tract continues developing and undergoes morphological and physiological changes that improve digestion and absorption of food (Maiorka et al, 2003 andMaiorka et al, 2006). Rizk and Ibrahim (2014) reported that live weight and feed intake as well as weight gain and feed conversion ratio were significantly improved by early feeding as compared to late feeding.…”
Section: Growth Performancementioning
confidence: 59%
“…Lipase activity was also influenced by the neonatal supplement (p < 0.05), and the non-parametric Kruskal-Wallis test was used to evaluate the dataStudies indicate that the activity of amylase and lipase oscillates during the life of the bird, and the peak can be reached at eight days of age (Maiorka, Dahlke, & Morgulis, 2006 The higher activity of pancreatic enzymes is related to the higher relative weight of the pancreas, so the presence of substrate and enzymatic activity are due to maturation of the pancreas (Moraes et al, 2008). The specific activity of lipase presented a distinct behavior when compared to the specific activity of amylase, because through the results obtained here the lipase activity was low.…”
Section: Resultsmentioning
confidence: 99%